Analisis Kualitas Pelayanan Publik dalam Pengurusan Surat Tanda Nomor Kendaraan (STNK) di Kantor Samsat Kabupaten Pakpak Bharat Provinsi Sumatera Utara - Manurung, Rosnita Nauli; Jamil, Bahrum; Deliana, Marlina (Universitas Medan Area, 2024)
Public services are services in the form of actions from the government as service providers who provide services to the community as service recipients. The background in this study is that there are still problems with public services that are not good and will not create community satisfaction, from where it can be concluded and used as a benchmark in realizing community satisfaction with the services provided, agencies and the government must be able to provide the best service. possible by evaluating aspects of the quality of existing services. This study aims to determine how the service system provided at the SAMSAT Office in providing services to the community. This type of research is qualitative research. Informants of this research are the public and employees, data collection uses observation, interviews, and documentation. The results of the study show the quality of public services in the management of Vehicle Registration Certificates at the SAMSAT Office of Pak-Pak Bharat Regency seen from the community satisfaction survey, namely: requirements, mechanisms and procedures, completion time, costs/tariffs, product specifications, types of services, competence of implementers, behavior of implementers, handling complaints, suggestions and inputs, facilities and infrastructure have been realized quite well and a service improvement strategy is still needed. The SAMSAT office has also completed a community satisfaction survey by providing a suggestion box and a satisfied and dissatisfied box which is an index of community satisfaction.